Has modern architecture failed? - Omer, Spahic (IIUM, 2019)
In the midst of all the developments associated with the emergence of modernity, architecture as a system of thought and a physical framework that outlines and frames human lives, was significantly affected. That was due to a tenet according to which changes in social systems, in cultural maturity and in people’s way of thinking and their beliefs, inevitably lead to changes in ways people perceive, build and experience their built environment. The former is the cause, the latter the effect. Moreover, the latter represents an embodiment and physical expression of the former. Hence, the various domains of people’s built environment denote a depository of frozen ideas, initiatives and solutions, as well as a succession of exhibition pathways where the level of people’s artistic and architectural consciousness and creativity has been immortalized and permanently displayed. Architecture is an open book about people, affirming their identity and their cultural together with civilizational proclivities and achievements. Developments in architecture are symptomatic of wider general trends.